Cellulase activity of bacteria isolated from water of mangrove ecosystem in Aceh Province - Irma Dewiyanti; Darmawi Darmawi; Zainal Abidin Muchlisin; Teuku Zahrial Helmi; Iko Imelda Arisa; Cut Nanda Defira; Fitriyani Fitriyani; Sawva Yura (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Cellulolytic bacteria that produce cellulase enzymes play an essential role in degrading cellulose in their habitat. The presence of cellulolytic bacteria strongly supports the fertility and productivity in mangrove waters. The objectives of the study are to analyze the activity of cellulase enzyme qualitatively through the cellulolytic index and quantitatively through the activity and specific activity of the cellulase enzyme from bacteria isolated from the water of mangrove ecosystems in Aceh Province. The qualitative experiment of enzyme activity was carried out at the Microbiology laboratory SKIPM Aceh, and a quantitative experiment of enzyme activity was conducted at the Microbiology Laboratory, Biology Department, IPB. Isolation of cellulolytic bacteria isolated from mangrove water used Carboxy Methyl Cellulose (1% CMC) selective media and carried out by spread plate method. The ability of bacteria to produce cellulase was tested qualitatively using the spot technique, this test was carried out using 1% Congo Red. Furthermore, the quantitative testing of cellulase enzymes activity adopted the DNS spectrophotometric method. The specific activity of the cellulase enzyme can be determined by using the Lowry method. There were 21 isolates that had a clear zone and had the ability to produce cellulase enzymes from 49 isolates that were successfully purified. The highest cellulolytic index (CI) produced using BAM421 isolate with the value of 5.50 was included in the high category, followed by BAM326 and BAM132 isolates, with values of 1.55 and 1.05 were categorized into the medium category. The other isolates were in the low cellulolytic index category. The isolate with the highest CI value was further tested using the quantitative enzyme activity test. The highest cellulase enzyme activity of BAM421 occurred at 24hr (0.0029 U/ml). The highest specific cellulase activity of BAM421 was at 24hr with the value of 0.210 U/mg. The result concluded that the qualitative test showed CI values can be categorized into low, medium, and high. Moreover, the value of the quantitative assay described that the cellulase enzyme and the specific enzyme activities of the bacteria were low in the study area.Keywords:Cellulolytic indexQuantitative testMangrove watersCellulase enzymeMicroorganismTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//